2019
DOI: 10.1089/lrb.2018.0035
|View full text |Cite
|
Sign up to set email alerts
|

Small Peptide Modulation of Fibroblast Growth Factor Receptor 3-Dependent Postnatal Lymphangiogenesis

Abstract: Background: The fibroblast growth factor receptor (FGFR) family includes transmembrane receptors involved in a wide range of developmental and postdevelopmental biologic processes as well as a wide range of human diseases. In particular, FGFR3 has been implicated in the mechanism by which 9-cis retinoic acid (9-cisRA) induces lymphangiogenesis and improves lymphedema. The purpose of this study was to validate the efficacy of a novel small peptide FGFR3 inhibitor, peptide P3 (VSPPLTLGQLLS), and to elucidate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…In vivo, the P3 peptide was able to rescue the viability of mice with the strong activating Thanatophoric dysplasia type II (TDII) mutation (Jin et al, 2012). The P3 peptide was able to inhibit FGFR3-mediated 9-cis retinoic acid (9-cisRA)-stimulated lymphatic EC proliferation in vitro and 9-cisRA-induced tracheal lymphangiogenesis in vivo (Perrault et al, 2019).…”
Section: Peptide Inhibitorsmentioning
confidence: 99%
“…In vivo, the P3 peptide was able to rescue the viability of mice with the strong activating Thanatophoric dysplasia type II (TDII) mutation (Jin et al, 2012). The P3 peptide was able to inhibit FGFR3-mediated 9-cis retinoic acid (9-cisRA)-stimulated lymphatic EC proliferation in vitro and 9-cisRA-induced tracheal lymphangiogenesis in vivo (Perrault et al, 2019).…”
Section: Peptide Inhibitorsmentioning
confidence: 99%
“…(Choi et al, 2012;Wong, 2021) 9-cis RA treatment also effectively prevented the development of postsurgical lymphedema in a mouse hindlimb model of lymphedema by promoting the formation of collateral lymphatics by activating FGFR signaling. (Jin et al, 2012;Bramos et al, 2016;Perrault et al, 2019;Daneshgaran et al, 2020) Despite the exciting developments in bench-to-bedside research throughout the past decade, it is important to address the gaps in current clinical trials, including relatively small patient cohorts and lack of standardized and reproducible outcome measures. These challenges and shortcomings are nicely reviewed in other manuscripts.…”
Section: Other Lymphangiogenic Growth Factorsmentioning
confidence: 99%
“…29 Finally, research at our institution has successfully identified retinoic acid as an FDA-approved therapeutic agent that may be repurposed for the novel indication of lymphedema prevention. [30][31][32][33] Beyond the laboratory, our clinical practice has produced several high-impact publications that cover the impact of surgical physiologic treatment modalities. The goal of this research is to produce more streamlined patient care algorithms based on evidence-based objective metrics and patient-reported outcomes to improve overall quality of life for individuals suffering from lymphedema.…”
Section: Research: the Main Drive For Better Treatmentsmentioning
confidence: 99%